2019
DOI: 10.1186/s42483-018-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

NAC transcription factors in plant immunity

Abstract: The NAC (NAM, ATAF and CUC) family is one of the largest plant-specific transcription factor (TF) families. Members of this family are implicated in plant growth, development and stress responses. Recent functional studies demonstrate that a number of NAC TFs function as positive or negative regulators of plant immunity to biotrophic, hemibiotrophic or necotrophic pathogens, as modulators of the hypersensitive responses and stomatal immunity or as virulence targets of pathogen effectors. They affect plant immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(143 citation statements)
references
References 109 publications
(180 reference statements)
3
139
0
1
Order By: Relevance
“…Many studies showed that a number of NAC TFs play dual roles in plant immunity against various pathogens through the hypersensitive responses and ETI [87]. A wheat TF TaNAC8 has a positive role to protect plants against the stripe rust pathogen infection [88].…”
Section: Function and Expression Pattern Of Nac Tfs Under Biotic Strementioning
confidence: 99%
“…Many studies showed that a number of NAC TFs play dual roles in plant immunity against various pathogens through the hypersensitive responses and ETI [87]. A wheat TF TaNAC8 has a positive role to protect plants against the stripe rust pathogen infection [88].…”
Section: Function and Expression Pattern Of Nac Tfs Under Biotic Strementioning
confidence: 99%
“…33 NAC genes changed significantly under salt stress. In Oryza sativa, 40 NAC genes were found to express under salt and drought stress (Yuan et al, 2019).…”
Section: Role Of Cis-regulatory Elements In Plant Abiotic Stress Respmentioning
confidence: 99%
“…In tobacco, SINAC35 improved resistance to leaf curl virus in transgenic tobacco. In rice, OsEREBP1, which binds to the ethylene-responsive element (ERF) GAGCCGCC, has been reported to be expressed in Magnaporthe grisea (Yuan et al, 2019). In glycine max, GmERF5/GmERF113 was found to express by the attack of Phytophthora sojae.…”
Section: Role Of Cis-regulatory Elements In Plant Biotic Stress Responsementioning
confidence: 99%
“…NAC: The NAC domain spans approximately 150 amino acids, and has five conserved subdomains (N1-N5) that form motifs for protein-protein interaction, DNA binding, or TF dimerization. Structural studies have shown that DBD is located at N-terminal while regulatory domain is located at the C-terminal [19,20]. DOF: The Dof domain is bi-functional domain, having dual activity for DNA-binding as well as protein-protein interaction.…”
Section: Structure Function and Mechanism Of Action Of Various Groumentioning
confidence: 99%